Photoresist composition, wavelength conversion layer, and method for preparing and using the same
Patent Information
- Application Number
- CN202610813347.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-09-04
AI Technical Summary
1、量子点光致发光效率下降,器件亮度衰减;
[0014]与现有技术相比,本发明的有益效果至少在于:
Smart Images

Figure CN122690885A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor display technology, specifically relating to a photoresist composition, a wavelength conversion layer with an in-situ generated cavity structure and its preparation method, and its application in Micro LED display devices. Background Technology
[0002] Micro LED display technology is considered an important direction for the development of next-generation display technology due to its advantages such as high brightness, high contrast, low power consumption, and long lifespan. In Micro LED display devices, quantum dots (QDs) or phosphors are typically used as wavelength conversion materials to convert the blue light emitted by the Micro LED chip into red and green light to achieve full-color display.
[0003] Currently, in existing technologies, quantum dot wavelength conversion layers are typically formed by dispersing quantum dots in a resin or photoresist system and then achieving pixel-level patterning through processes such as spin coating, exposure, development, and post-baking. However, in the actual operation of MicroLED display devices, due to the high heat density of the light-emitting chip, the quantum dot conversion layer is exposed to a high-temperature environment for extended periods, which can easily lead to the following problems: 1. The photoluminescence efficiency of quantum dots decreases, leading to a reduction in device brightness; 2. Desorption or decomposition of ligands on the surface of quantum dots leads to unstable optical properties; 3. Pixel-level light emission uniformity deteriorates, affecting display quality.
[0004] To mitigate the heat conduction problems mentioned above, some existing technologies typically introduce a separate heat-insulating or scattering structure layer between the light-emitting unit and the wavelength conversion layer of a Micro LED display device, such as a pre-fabricated hollow microsphere thin film structure, to reduce heat transfer to the wavelength conversion layer. However, this type of solution usually has the following drawbacks: 1. An additional independent functional layer needs to be introduced, which not only increases the complexity of the process, but also the prefabricated hollow microspheres are introduced as foreign objects. Their bonding force with the substrate interface is weak, which can easily disrupt the continuous light emission path of the wavelength conversion material and cause significant optical scattering loss. 2. Poor compatibility with existing photolithography patterning processes; 3. It is difficult to achieve stable implementation in pixel-level fine structures.
[0005] Therefore, there is an urgent need for a wavelength conversion layer structure that can achieve internal thermal isolation and maintain the continuous distribution of functional materials without adding additional device layers or changing the existing Micro LED patterning process. Summary of the Invention
[0006] The main objective of this invention is to provide a photoresist composition for Micro LED wavelength conversion and a wavelength conversion layer with an in-situ generated cavity structure and a method for preparing the same, so as to overcome the shortcomings of the prior art.
[0007] Another object of the present invention is to provide applications of the wavelength conversion layer.
[0008] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: This invention provides a photoresist composition comprising: Photoresist resin matrix; Wavelength conversion material dispersed in the photoresist resin matrix; Thermally decomposable components dispersed in the photoresist resin matrix; The thermally decomposable component remains stable during the patterning process and decomposes and releases gas during the heat treatment process to form a cavity structure inside the photoresist resin matrix. The cavity structure is filled with the gas generated by pyrolysis, and the refractive index difference Δ between the cavity structure and the photoresist resin matrix is ≥0.4.
[0009] This invention also provides a wavelength conversion layer having multiple independent cavity structures inside, the cavity structures being formed by in-situ decomposition of the thermally decomposable components in the photoresist composition through heat treatment.
[0010] In some implementations, the wavelength conversion layer specifically includes: A photoresist pixel unit formed by curing a resin containing a POSS hybrid framework, the photoresist pixel unit having a nano-confined space formed by the POSS hybrid framework; The in-situ formed closed-cavity structure is uniformly distributed inside the photoresist pixel unit; The closed-cell cavity structure is formed by the in-situ pyrolysis of thermally decomposable components within the confined space of the POSS-containing hybrid framework during heat treatment. The POSS-containing hybrid framework restricts the excessive growth and merging of the cavity structure. The closed-cell cavity structure is filled with gas generated by pyrolysis.
[0011] This invention also provides a method for fabricating a wavelength conversion layer, comprising: Wavelength conversion material and thermally decomposable components are dispersed in a photoresist resin matrix to form the aforementioned photoresist composition; The photoresist composition is coated onto a substrate; The photoresist composition is patterned to form a patterned wavelength conversion layer; The patterned wavelength conversion layer is subjected to heat treatment to decompose the thermally decomposable components and form a cavity structure in situ inside the wavelength conversion layer.
[0012] This invention also provides the application of the photoresist composition or wavelength conversion layer in the fabrication of Micro LED display devices.
[0013] Accordingly, embodiments of the present invention also provide a Micro LED display device, comprising: Light-emitting unit; A wavelength conversion layer disposed on the light-emitting unit, wherein the wavelength conversion layer is the aforementioned wavelength conversion layer, or the wavelength conversion layer is fabricated on the light-emitting unit according to the aforementioned fabrication method.
[0014] Compared with the prior art, the beneficial effects of the present invention are at least as follows: 1) This invention forms a cavity structure by in-situ decomposition of thermally decomposable components inside the wavelength conversion layer. By utilizing the low thermal conductivity of the gas inside the cavity, the thermal conduction efficiency of the light-emitting unit into the wavelength conversion layer is effectively reduced, thereby improving the thermal stability of the wavelength conversion material and reducing the problems of light emission efficiency decay and ligand desorption caused by high temperature. Furthermore, the refractive index difference between the cavity structure and the photoresist resin matrix can generate strong interface scattering, increasing the optical path of blue light in the wavelength conversion layer, thereby improving the blue light absorption rate and wavelength conversion efficiency. 2) The cavity structure formed in situ in this invention does not require the introduction of an independent pre-fabricated heat insulation layer, keeping the existing MicroLED photolithography patterning process unchanged and reducing the complexity of the process; and the cavity structure does not penetrate the upper and lower surfaces to form a closed-hole shape, ensuring the mechanical integrity of the wavelength conversion layer. 3) The hole walls of in-situ formed holes are the matrix resin itself. The wavelength conversion material can be continuously distributed in the resin matrix and distributed around the cavity structure. The cavity structure is located inside the photoresist resin matrix, which does not destroy the continuous light emission path of the wavelength conversion material. This avoids the defects such as poor interface bonding and optical scattering loss caused by the introduction of pre-fabricated hollow microspheres as foreign objects, and easy to cause blockage or rough development edges due to poor interface compatibility during photolithography and development. It maintains optical continuity and improves the light emission stability and service life of Micro LED display devices. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a SEM cross-sectional image of the quantum dot wavelength conversion layer prepared in Example 1 of this invention; Figure 2 This is a SEM cross-sectional image of the quantum dot wavelength conversion layer prepared in Example 4 of this invention; Figure 3 This is a SEM cross-sectional image of the quantum dot wavelength conversion layer prepared in Example 5 of this invention; Figure 4 This is a SEM cross-sectional image of the quantum dot wavelength conversion layer prepared in Example 6 of this invention; Figure 5 and Figure 6 This is a SEM cross-sectional image of the quantum dot wavelength conversion layer prepared in Comparative Example 1. Detailed Implementation
[0017] In view of the problem that the quantum dot photoresist conversion layer in the prior art is prone to thermal quenching under high temperature operating environment, which leads to the decay of luminous efficiency and shortened lifespan, the inventors of this case, through long-term research and extensive practice, have proposed the technical solution of the present invention. The main invention is to propose a photoresist composition, a wavelength conversion layer with an in-situ generated cavity structure and its preparation method. By forming a cavity structure in situ inside the photoresist to reduce the thermal conductivity, the thermal stability and optical performance of quantum dots in Micro LED display devices are improved, while maintaining good compatibility with existing photolithography processes.
[0018] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Specifically, as one aspect of the technical solution of this invention, a photoresist composition for Micro LED wavelength conversion includes: Photoresist resin matrix; Wavelength conversion material dispersed in the photoresist resin matrix; Thermally decomposable components dispersed in the photoresist resin matrix; The thermally decomposable component remains stable during the patterning process and decomposes and releases gas during the heat treatment process to form a cavity structure inside the photoresist resin matrix. The cavity structure is filled with the gas generated by pyrolysis, and the refractive index difference Δ between the cavity structure and the photoresist resin matrix is ≥0.4.
[0020] Furthermore, the refractive index difference between the cavity structure and the photoresist resin matrix can generate strong interface scattering. After entering the conversion layer, blue light will undergo multiple total internal reflections and Mie scatterings at the cavity interface, increasing the effective optical path of blue light in the wavelength conversion layer, thereby improving the blue light absorption rate and wavelength conversion efficiency, which is macroscopically manifested as a decrease in luminous efficiency attenuation.
[0021] The above-mentioned solution of the present invention introduces a thermally decomposable component into the photoresist composition and utilizes its in-situ decomposition characteristics during the heat treatment process to form a cavity structure inside the photoresist resin matrix. This cavity structure can effectively block the heat conduction path to the wavelength conversion material, thereby significantly improving the thermal stability of the quantum dot photoresist conversion layer without adding additional process steps.
[0022] In some embodiments, the decomposition temperature of the thermally decomposable component is higher than the glass transition temperature of the photoresist resin matrix after curing. Further, the thermally decomposable component decomposes during hardening or post-baking processes at temperatures above a predetermined level, releasing gases and forming cavity structures within the photoresist.
[0023] In some embodiments, the decomposition temperature of the thermally decomposable component is higher than the temperature of the patterning process (photoresist exposure and development process, etc.), that is, it remains stable under photolithography exposure and development conditions.
[0024] By defining the relationship between the decomposition temperature and the glass transition temperature, this invention ensures that the polymer matrix has formed a rigid network with high modulus and low fluidity before the gas is released. The skeleton has sufficient strength when forming pores, thereby locking the gas in place to form a stable cavity and avoiding pore collapse or merging.
[0025] The unexpected effects of this invention, which utilizes specific thermally decomposable components, are manifested in the following three aspects: (1) Synergy between in-situ topography locking and pixel precision: In micrometer-scale pixels (e.g., 5µm × 5µm), ordinary pore-forming agents undergo macroscopic deformation during degassing, resulting in pixel chamfering or jagged edges. However, when certain thermally decomposable components decompose, the internal pressure generated by the breakage of their molecular chains reaches a nanometer-scale dynamic equilibrium with the constraint force of the POSS-containing hybrid framework, making the critical size (CD) loss of the pixel almost zero. (2) The "cold chamber" effect at the wavelength conversion material interface: Conventional pore-forming methods may expose wavelength conversion materials directly to air. After the specific thermally decomposable components of this invention are pyrolyzed, they leave an extremely thin carbon residue or passivation layer on the inner wall of the cavity. This structure not only provides a thermally insulated cavity, but also unexpectedly provides secondary encapsulation for the wavelength conversion material, significantly improving its fluorescence lifetime at high temperatures.
[0026] (3) Gain of total internal reflection: Ordinary holes can lead to light scattering loss. In this invention, because the hole size is precisely controlled at the 100~500 nm level, the structure reduces the refractive index and achieves Mie scattering enhancement, which in turn guides more blue light into the quantum dot and improves the light conversion efficiency.
[0027] In some embodiments, the thermally decomposable component may include one or a combination of two of thermally decomposable polymers, thermally decomposable small molecules, etc., but is not limited thereto. Compared with thermally decomposable polymers, thermally decomposable small molecules have the advantage of smaller molecular size, enabling finer nanoscale pore size control, and often have more defined abrupt decomposition temperatures.
[0028] In some embodiments, the size of the thermally decomposable component is in the nanometer or micrometer range.
[0029] In some preferred embodiments, the shape of the pyrolytic component can be spherical, quasi-spherical, amorphous, fibrous, or even a core-shell structure. Further, the average particle size (D) of the pyrolytic component... 50 The wavelength range is 50~300 nm.
[0030] In some preferred embodiments, the thermally decomposable polymer may include one or more combinations of polypropylene carbonate, polymethyl methacrylate, polynorbornene polymers, polyterephthalaldehyde, tert-butyloxycarbonyl modified copolymers, etc., preferably polypropylene carbonate, but not limited thereto.
[0031] Specifically, polypropylene carbonate (PPC) is the ideal thermally decomposable site-filling material, with a decomposition temperature window between 180 and 250°C. Its decomposition mechanism is "chain-end depolymerization," and the products are almost entirely converted into propylene carbonate monomers, carbon dioxide, and water, resulting in extremely low char residue (typically <1%). This extremely low residue ensures the chemical purity of the cavity's internal environment and prevents chemical poisoning of the wavelength conversion material surface. Preferably, the thermally decomposable polymer is polypropylene carbonate (PPC) nanoparticles with a weight-average molecular weight (Mw) of 50,000 to 150,000.
[0032] Polymethyl methacrylate (PMMA) is a thermally depolymerizable polymer with a decomposition temperature typically between 230 and 300°C (this temperature can be lowered to around 200°C by adjusting the molecular weight or introducing comonomers). It is usually prepared as monodisperse nanospheres and added to photoresist. Because it exists in a microsphere form, the resulting cavity geometry is highly regular, easily forming uniformly distributed monodisperse cavities, which is beneficial for precisely controlling the optical scattering path within Micro LED pixels. Preferably, the thermally decomposable polymer is polymethyl methacrylate nanospheres.
[0033] Polynorbornene polymers are Unity™ series or norbornene copolymers containing specific functional groups. By adjusting the substituents, their decomposition temperature can be precisely adjusted within the range of 200~420℃. These materials exhibit excellent mechanical stability, maintaining their morphology in the early stages of heat treatment until the set temperature is reached, at which point the morphology rapidly disappears.
[0034] Poly(terephthalaldehyde) has a low tip temperature and can even undergo avalanche decomposition at low temperatures (<150℃) under the triggering of specific catalysts or photoacids. It is suitable for quantum dot systems with extremely high heat sensitivity and can form cavities in a very short time, reducing the time that quantum dots are exposed to high temperatures.
[0035] The copolymer modified with tert-butyloxycarbonyl (Boc) utilizes a chemical degassing mechanism, in which the Boc group undergoes thermal side group removal at 150~180℃, releasing CO2 and isobutylene, which can exist as side chains of the resin, thus achieving molecular-level pore structure control.
[0036] In some implementations, for the hardening temperature range of Micro LED photoresist, the thermally decomposable small molecules are small molecules that are incompatible with the photoresist resin matrix at room temperature, and are dispersed through high shear to form a suspension system, thereby ensuring the independence of pore formation.
[0037] In some preferred embodiments, the pyrolytic small molecules may include one or more combinations of azo compounds, carbonate compounds, bicarbonate compounds, tert-butyl ester compounds induced by thermal acid generators, organic peroxides, etc., but are not limited thereto.
[0038] Specifically, azo compounds are the most common thermal decomposition gas-releasing agents, producing nitrogen gas through the thermal breaking of nitrogen-nitrogen bonds. Typical examples include azobisisobutyronitrile (AIBN) and azodicarbonamide (ADC / AC). Their decomposition temperature is typically between 100 and 200°C, releasing pure N2 after decomposition. They have almost no chemical activity towards quantum dots and are very safe.
[0039] Carbonate and bicarbonate compounds release carbon dioxide and water vapor through thermal decomposition. Specific examples include ammonium carbonate, ammonium bicarbonate, and ammonium oxalate. The decomposition temperature is relatively low (approximately 60-150°C). Because the products are entirely gaseous and highly volatile, pore formation can be achieved in the early stages of post-baking. However, encapsulation (e.g., microencapsulation) or chemical modification is necessary to prevent premature decomposition during the pre-baking stage before development.
[0040] The addition of a thermogenic acid generator (TAG) induces the release of strong acids from uncoated small molecules upon heating, causing unstable groups on the matrix or additives to detach. These groups can be tert-butyl carbonates, tert-butyl esters, etc. When the temperature reaches 150–180°C, the t-Boc groups undergo acid-catalyzed thermal degradation, releasing CO2 and isobutylene gas. This small molecule release mechanism is often accompanied by a transformation of the chemical structure, which can significantly alter the local polarity of the pore walls, contributing to the stable dispersion of quantum dots.
[0041] Typical organic peroxides are benzoyl peroxide (BPO) and di-tert-butyl peroxide (DTBP), which undergo free radical cleavage at 100-150°C.
[0042] In some embodiments, the wavelength conversion material may include one or more combinations of quantum dots, phosphors, perovskite nanomaterials, etc., but is not limited thereto.
[0043] In some preferred embodiments, the quantum dot may be a red quantum dot or a green quantum dot, etc.
[0044] In some embodiments, the photoresist resin matrix is a resin matrix containing a POSS hybrid framework. The higher the functionality of the POSS, the harder the framework, and the closer the size of the resulting cavity structure is to the nanoscale. Further, in the resin matrix containing the POSS hybrid framework, the functionality of the POSS is 6-12, for example, 6, 8, 10, or 12, preferably a high-functionality multifunctional silsesquioxane. High functionality allows for the construction of a high-modulus three-dimensional rigid scaffold during crosslinking.
[0045] In some embodiments, the wavelength conversion material content in the photoresist composition is 10-40 wt% (to ensure brightness), and the content of the thermally decomposable component is 1-15 wt%. The content of the thermally decomposable component determines the porosity; excessive loading can lead to pixel cracking and also affect development accuracy and mechanical strength.
[0046] As another aspect of the technical solution of the present invention, it also relates to a wavelength conversion layer having multiple independent cavity structures inside, wherein the cavity structures are formed by the in-situ decomposition of the thermally decomposable components in the photoresist composition through heat treatment.
[0047] In some implementations, the wavelength conversion layer specifically includes: A photoresist pixel unit is formed by curing a resin containing a POSS hybrid framework. The photoresist pixel unit has a nano-confined space formed by the POSS (silsesquioxane) hybrid framework. The POSS hybrid framework forms a rigid cross-linked network (which inhibits bubble collapse or over-expansion). Its edge critical size loss is ≤5%. The in-situ formed closed-cavity structure is uniformly distributed inside the photoresist pixel unit; Wavelength conversion material is continuously distributed in the photoresist pixel unit and distributed around the closed-hole cavity structure; The closed-cell cavity structure is formed by the in-situ pyrolysis of thermally decomposable components within the confined space of the POSS-containing hybrid framework during heat treatment. The POSS-containing hybrid framework restricts the excessive growth and merging of the cavity structure. The closed-cell cavity structure is filled with gas generated by pyrolysis.
[0048] In some preferred embodiments, the cavity structure is dispersed within the wavelength conversion layer and does not penetrate the upper and lower surfaces of the wavelength conversion layer.
[0049] In some preferred embodiments, the cavity structure is nanometer-scale or micrometer-scale in size.
[0050] Furthermore, the average diameter of the cavity structure is 100~500 nm. Due to the instantaneous pressure of the gas generated during pyrolysis and the microscopic viscoelasticity of the resin matrix at the heat treatment temperature, the diameter of the formed cavity structure is slightly larger than the initial particle size of the thermally decomposable component.
[0051] In some embodiments, the cavity structure accounts for 5-25% of the volume of the wavelength conversion layer.
[0052] In some implementations, the thickness of the wavelength conversion layer is 1 to 10 μm.
[0053] As another aspect of the technical solution of the present invention, it also relates to a method for preparing a wavelength conversion layer, which includes: Wavelength conversion material and thermally decomposable components are dispersed in a photoresist resin matrix to form the aforementioned photoresist composition; The photoresist composition is coated onto a substrate; The photoresist composition is patterned to form a patterned wavelength conversion layer; The patterned wavelength conversion layer is subjected to heat treatment to decompose the thermally decomposable components and form a cavity structure in situ inside the wavelength conversion layer.
[0054] In some implementations, the cavity structure is formed after the patterning process is completed on the wavelength conversion layer.
[0055] In some embodiments, the heat treatment is a hardening process. The hardening process is a segmented heating heat treatment, comprising: first heating at a rate of 1-5 °C / min to 100-140 °C and holding for 10-20 min; then heating at a rate of 0.5-3 °C / min to 150-230 °C, preferably 180-230 °C, and holding for 20-40 min. The heating rate affects the pore wall morphology; slow heating is beneficial for obtaining complete closed pores. Further, the heating rate in the second heating stage is controlled at 0.5-3 °C / min, preferably 1-2 °C / min. This rate allows the generated gas molecules to be released slowly, preventing a sudden increase in internal pressure from breaking through the rigid POSS framework.
[0056] In other embodiments, the hard film process can also be achieved by directly heating at a constant temperature of 160~240°C for 15~60 minutes, skipping the low heating rate control and the first-stage low-temperature crosslinking process.
[0057] In some preferred embodiments, a method for fabricating a photoresist conversion layer with a cavity structure includes the following steps: 1) Disperse quantum dots and thermally decomposable components in photoresist resin to form a quantum dot photoresist composition; 2) Coat the quantum dot photoresist composition onto the surface of a Micro LED blue light-emitting unit; 3) Expose and develop the coated quantum dot photoresist to form a patterned quantum dot conversion layer; 4) The patterned quantum dot conversion layer is subjected to high-temperature hard film treatment to decompose the thermally decomposable components, thereby forming a cavity structure in situ inside the quantum dot photoresist conversion layer.
[0058] The formation mechanism of the cavity structure in this invention can be explained as a transition from "solid occupancy" to "constrained expansion." The formation of the cavity structure is a process driven by the breaking of chemical bonds and locked by physical and mechanical equilibrium.
[0059] First, the phased locking mechanism of this invention is as follows: 1. Pre-locking stage (patterning): At this stage, the thermally decomposable components exist in the form of solid particles, which play a "space occupancy" role and do not affect the photolithography accuracy. 2. Framework solidification stage (early stage of heat treatment): As the temperature rises, the POSS hybrid framework first undergoes deep cross-linking, the modulus increases rapidly, and a rigid "nanoscaffold" is formed. 3. In-situ decomposition stage (late heat treatment stage): when the temperature exceeds the decomposition point of the pore-forming agent, the solid component is converted into gas. Since the surrounding framework has been cured at this time, the gas is locked in situ and cannot move or coalesce, and finally a cavity structure with a size equivalent to the particle size of the original thermally decomposable component is formed. That is, the cavity structure is formed by pyrolysis of the thermally decomposable component in the restricted space of the POSS-containing hybrid framework during the late heat treatment stage.
[0060] II. Influence of thermal decomposition release rate on cavity structure morphology The release rate (v = dα / dt) determines whether the cavity structure is "smooth spherical" or "cracked void": Low-rate release (preferred): gas is generated slowly, and polymer segments have sufficient time to undergo local relaxation to adapt to internal pressure. The resulting cavity has a smooth wall, small stress concentration, and high mechanical strength of the material.
[0061] High-rate release: if the huge internal pressure generated instantaneously exceeds the yield strength of the POSS hybrid framework, microcracks will occur on the pore wall. Although the heat insulation effect may be improved, it will damage the sealing property of the wavelength conversion material, leading to invasion of water and oxygen and reduced reliability.
[0062] III. The characteristic size of the cavity structure is not randomly generated, but is strictly controlled by the following two parameters: the initial particle size of the thermally decomposable component (i.e., the pore-forming precursor) and the game (physical restriction) between matrix modulus and internal pressure. The generated independent closed cells can effectively block the conductive transfer of heat (tortuous path theory) without forming permeation channels for water and oxygen. This distribution forms a "gas-wavelength conversion material-polymer" micro heterogeneous structure. The gas cavity directly blocks phonon heat transfer from the Micro LED chip, thereby creating a "cold cabin" environment for the wavelength conversion material at the micro scale.
[0063] To achieve restricted pore formation, it must be ensured that before gas release, the polymer matrix has already formed a high-modulus, low-fluidity network through crosslinking reaction (that is, enters a glassy state or quasi-glassy state). If Td (decomposition temperature) < Tg (glass transition temperature): gas is released when the matrix is still in a liquid state or a high-fluidity rubbery state. Since there is no rigid framework support at this time, the internal pressure generated by the gas will drive large-scale migration of polymer segments, leading to pore coalescence, collapse, and even direct escape of gas from the surface, making it impossible to form a stable cavity structure. If Td (decomposition temperature) > Tg (glass transition temperature): the matrix is already in a "structurally frozen" state (glassy state) at this time. The thermally decomposable component decomposes surrounded by the rigid support, and the gas can only undergo restricted expansion within a very small nanometer-scale local range, thereby being locked in situ.
[0064] As another aspect of the technical solution of the present invention, it also relates to the application of the photoresist composition or wavelength conversion layer in the field of fabricating Micro LED display devices.
[0065] Accordingly, as another aspect of the technical solution of the present invention, it also relates to a Micro LED display device, which includes: Light-emitting unit; A wavelength conversion layer is disposed on the light-emitting unit, wherein the wavelength conversion layer is the aforementioned wavelength conversion layer or the wavelength conversion layer is fabricated on the light-emitting unit according to the aforementioned fabrication method.
[0066] In some implementations, the light-emitting unit is a Micro LED blue light-emitting unit.
[0067] The cavity structure is used to reduce the thermal conductivity of the Micro LED blue light-emitting unit to the inside of the photoresist conversion layer.
[0068] Compared to photoresist conversion layers without the cavity structure, the Micro LED display devices of the present invention exhibit higher luminous stability under high temperature or long-term operating conditions.
[0069] In summary, this invention utilizes a rigid cross-linked network pre-constructed within the photoresist containing a POSS hybrid framework to provide a nanoscale scaffold for subsequent thermal decomposition and pore formation. Unlike conventional porous materials, the pore formation process of this invention occurs during the hardening stage after photoresist patterning. At this point, the POSS hybrid framework has completely frozen the macroscopic morphology of the pixel, thereby ensuring that the internal pressure generated by gas release only forms cavities locally, without causing the collapse or dimensional shrinkage of the entire pixel unit.
[0070] This invention achieves thermal decoupling between the quantum dot luminescent micro-region and the high-heat-generating chip substrate at the microscale by constructing a nanocavity structure in situ. The cavity structure significantly increases the interfacial thermal resistance for phonon transmission, creating a stable thermal barrier without sacrificing transmittance. Simultaneously, based on the Effective Medium Theory (EMA), the non-uniform optical potential field formed by the low-refractive-index cavity and the high-refractive-index POSS hybrid framework induces micro-scattering behavior of the incident light, extending the coherent path of the excitation light within the wavelength conversion layer. This compensates for the non-radiative recombination loss of the quantum dots at high temperatures, ultimately achieving a high retention rate of luminescent efficiency under long-term high-temperature service conditions.
[0071] The technical solution of the present invention will be further described in detail below through specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, the experimental materials used in the embodiments below can be purchased from conventional biochemical reagent companies.
[0072] Example 1 A method for fabricating a quantum dot wavelength conversion layer with an in-situ closed-pore cavity structure includes the following steps: (1) Formulation of photoresist composition 1. 25% by mass of red CdSe / ZnS quantum dots (average particle size 10 nm, purchased from Beijing Beida Jubang Quantum Dot Technology Co., Ltd.) were dispersed in an acrylate photoresist resin matrix containing 45 wt% methacryloyl polyhedral oligomeric silsesquioxane (MAPOSS, functionality 8, purchased from Hybrid Plastics, USA).
[0073] 2. Introduction of thermally decomposable components: Add 6% by mass of polypropylene carbonate (PPC) nanoparticles (weight-average molecular weight MW = 100,000, average particle size D) to the above system. 50 The red quantum dot photoresist composition was formed by continuously stirring the material (120 nm, purchased from Merck Ltd.) at 3000 rpm for 30 min using a high-shear homogenizer and then ultrasonically dispersing it for 15 min.
[0074] (2) Graphical processing The prepared quantum dot photoresist composition was spin-coated onto the surface of a Micro LED blue light-emitting unit (target film thickness 5µm), followed by pre-baking at 100 °C for 3 min; and then subjected to ultraviolet exposure through a mask (exposure energy 1500 mJ / cm²). 2 The quantum dot wavelength conversion layer was developed with 0.238wt% TMAH developer for 60 seconds, rinsed and dried to form a patterned quantum dot wavelength conversion layer with a pixel size of 5*5um.
[0075] (3) Segmented hard film heat treatment: The substrate with the patterned quantum dot wavelength conversion layer is placed in a programmable temperature controlled oven.
[0076] First stage (skeleton curing): First, heat to 120 ℃ at a heating rate of 2 ℃ / min and hold for 15 min to allow the MAPOSS skeleton to undergo sufficient deep cross-linking curing and lock in the macroscopic morphology of the pixel. The second stage (in-situ pyrolysis): The temperature is then increased to 190 ℃ at a slow heating rate of 1.5 ℃ / min and held for 30 min. In this stage, the PPC nanoparticles undergo "chain-end depolymerization" and are completely vaporized. The gas undergoes confined micro-expansion within the solidified rigid nano-confined space. Finally, the temperature is reduced to room temperature at a rate of 2 °C / min.
[0077] The cavity structure within the quantum dot wavelength conversion layer obtained in this embodiment has an average diameter of 150 nm and exhibits a regular closed-pore spherical distribution (see [reference]). Figure 1 (SEM cross-sectional image shown), accounting for 12% of the volume. Tests show that the cavity structure is filled with carbon dioxide and water vapor generated by pyrolysis, and the refractive index difference Δ between the cavity structure (n≈1.00) and the photoresist resin substrate (n≈1.51) is 0.51. Tests show that the Micro LED display device based on this quantum dot wavelength conversion layer maintains a quantum dot luminous efficiency retention rate of up to 94.5% after 1000 hours of continuous operation at 120℃, with significantly reduced luminous efficiency decay, pixel CD loss of less than 3%, smooth pixel edges, and no pixel chipping.
[0078] Example 2 The difference between this embodiment and Example 1 is that the thermally decomposable component, polypropylene carbonate (PPC) nanoparticles, is replaced with thermally degradable small molecules. The specific steps are as follows: (1) Formulation of photoresist composition 20% by mass of green InP / ZnS quantum dots were dispersed in the same MAPOSS (functionality 8) acrylate photoresist matrix as in Example 1. Subsequently, 4% by mass of azodicarbonamide (ADC, average particle size D) was added. 50 The ADC (75 nm, purchased from Merck Ltd.) was used as a pyrolytic small molecule. At room temperature, this ADC small molecule was incompatible with the resin matrix. It was dispersed at 4000 rpm for 40 min using a high-shear dispersion device to form a green quantum dot photoresist composition.
[0079] (2) Graphical processing Similar to Example 1, spin coating, pre-baking, exposure and development were performed on the surface of the Micro LED chip to obtain a fine green pixel pattern (target film thickness of 6µm).
[0080] (3) Segmented hard film heat treatment: First stage: First, heat up to 110 ℃ at 5 ℃ / min and hold for 20 min to allow the resin matrix and POSS skeleton to initially crosslink and form a rigid network; Second stage: Subsequently, the temperature was increased to 210 ℃ at a slow heating rate of 1.0 ℃ / min and held for 25 min. At this time, the ADC small molecules underwent thermal shear fracture, rapidly releasing pure N2 gas, which formed pores in situ under the confinement of the solidified network; After heat treatment, allow it to cool naturally to room temperature.
[0081] The cavity structure within the quantum dot wavelength conversion layer obtained in this embodiment has an average diameter of 110 nm, a morphology of uniformly distributed independent closed pores, and a volume percentage of 8%. The refractive index difference Δ between the cavity structure and the photoresist resin substrate is 0.49. Testing showed that after 1000 hours of continuous operation at 120 °C, the device maintained a quantum dot luminous efficiency of 92.1%, exhibiting excellent thermal barrier performance. Furthermore, the pixel CD loss was less than 4%, and the pixel edges were smooth with no pixel chipping.
[0082] Example 3 This embodiment demonstrates a process for molecular-level pore control using chemical structure transformation: (1) Formulation of photoresist composition A system containing 40 wt% epoxy-Polyhedral oligomeric silsesquioxane (Epoxy-POSS, functionality 8) as an alicyclic epoxy resin matrix was selected, and 30 wt% of red perovskite nanomaterials (a mixture of CsPbBr3 and CsPbI3) were added. Next, 5 wt% of a copolymer modified with tert-butoxycarbonyl groups (t-Boc side chain modified, purchased from Maclean's Reagents) and 1 wt% of a thermally decomposable acid generator (TAG-2690, purchased from Maclean's Materials) were introduced as thermally decomposable components, and the mixture was dispersed uniformly by high-speed stirring.
[0083] (2) Graphical processing The substrate was coated and patterned using the same photolithography process as in Example 1 (target film thickness was 4 µm).
[0084] (3) Segmented hard film heat treatment: First stage: Increase the temperature to 105 ℃ at 3 ℃ / min and hold for 15 min to lock the pixel morphology and promote the pyrolysis activation of TAG, releasing a strong acid environment locally inside the matrix. The second stage involved heating to 165 °C at a rate of 1.2 °C / min and holding at that temperature for 35 min. Under strong acid catalysis and high-temperature co-catalysis, the t-Boc group underwent avalanche thermal side-group removal, releasing CO2 and isobutylene gases. Since perovskite nanomaterials are temperature-sensitive, this temperature range (<170 °C) successfully prevented thermal damage to the functional materials.
[0085] After heat treatment, allow it to cool naturally to room temperature.
[0086] The cavity structure within the quantum dot wavelength conversion layer obtained in this embodiment has an average diameter of 130 nm and a volume fraction of 10%. The refractive index difference Δ between the cavity structure and the photoresist resin substrate is 0.50. Testing showed that, due to successful avoidance of high-temperature thermal damage to the perovskite material, the device maintained a luminous efficiency of 95.2% after 1000 hours of continuous operation at 120 °C. Furthermore, the pixel CD loss was less than 2%, and the pixel edges were excellent.
[0087] Example 4 Except for the heating rate during heat treatment, the materials and steps in this embodiment are exactly the same as in Example 1: (1) The photoresist composition was prepared in the same manner as in Example 1.
[0088] (2) Graphical processing, the same as in Example 1.
[0089] (3) Heat treatment (rapid heating): The patterned quantum dot conversion layer, after development and drying, was directly placed in a rapid drying oven preheated to 190 ℃ and heated at a constant temperature of 190 ℃ for 30 minutes, skipping the low heating rate control and the first stage of low-temperature crosslinking process.
[0090] See the schematic SEM cross-sectional image of the quantum dot wavelength conversion layer obtained in this embodiment. Figure 2 As shown, due to the instantaneous release of gas, local coalescence occurred, increasing the average diameter to 350 nm, and microcracks appeared in some hole walls, accounting for 15% of the volume. The refractive index difference Δ between the cavity structure and the photoresist resin substrate was 0.51. After testing, the device maintained a luminous efficiency of 85.3% after 1000 hours of continuous operation at 120 °C. This is because the lack of segmented slow heating control and the microcracks in the hole walls led to a small amount of water and oxygen intrusion. Its thermal stability and long-term lifetime are slightly lower than Example 1, but still significantly better than Comparative Example 1 without a pore-forming agent.
[0091] Example 5 The difference between this embodiment and Embodiment 1 is that: (1) Formulation of photoresist composition The thermally decomposable component, polypropylene carbonate (PPC) nanoparticles, was replaced with polymethyl methacrylate (PMMA). The mass fraction of red CdSe / ZnS quantum dots was adjusted to 10%, and the mass fraction of PMMA was 1%.
[0092] (2) Graphical processing, same as in Example 1.
[0093] (3) Segmented hard film heat treatment: First stage (skeleton curing): First, heat to 100 ℃ at a heating rate of 1 ℃ / min and hold for 20 min; Second stage (in-situ pyrolysis): Then, the temperature is increased to 180 ℃ at a slow heating rate of 0.5 ℃ / min and held for 40 min.
[0094] The cavity structure within the quantum dot wavelength conversion layer obtained in this embodiment has an average diameter of 220 nm and exhibits a regular closed-pore spherical distribution (see [reference]). Figure 3 (SEM cross-sectional image shown), accounting for 5% of the volume. The refractive index difference Δ between the cavity structure and the photoresist resin substrate is 0.48. Testing revealed that the Micro LED display device based on this quantum dot wavelength conversion layer maintained a quantum dot luminous efficiency of up to 89.5% after 1000 hours of continuous operation at 120 °C, with pixel CD loss of less than 3% and smooth pixel edges.
[0095] Example 6 The difference between this embodiment and Embodiment 1 is that: (1) Formulation of photoresist composition The thermally decomposable component, polypropylene carbonate (PPC) nanoparticles, was replaced with poly(terephthalaldehyde). The mass fraction of red CdSe / ZnS quantum dots was adjusted to 40%, and the mass fraction of polymethyl methacrylate was 15%.
[0096] (2) Graphical processing, same as in Example 1.
[0097] (3) Segmented hard film heat treatment: First stage (skeleton curing): First, heat to 140 ℃ at a heating rate of 2 ℃ / min and hold for 10 min; Second stage (in-situ pyrolysis): Then, the temperature is increased to 230 ℃ at a slow heating rate of 3 ℃ / min and held for 20 min.
[0098] The cavity structure within the quantum dot wavelength conversion layer obtained in this embodiment has an average diameter of 280 nm and exhibits a regular closed-pore spherical distribution (see [reference]). Figure 4 (SEM cross-sectional image shown), accounting for 22% of the volume. The refractive index difference Δ between the cavity structure and the photoresist resin substrate is 0.52. Testing revealed that the Micro LED display device based on this quantum dot wavelength conversion layer maintained a quantum dot luminous efficiency of up to 91% after 1000 hours of continuous operation at 120 °C, with pixel CD loss of less than 4% and smooth pixel edges.
[0099] Comparative Example 1 (without pore-forming agent) Compared to Example 1, this comparative example is used to provide a basic performance comparison: (1) Formulation of photoresist composition Red CdSe / ZnS quantum dots with a mass fraction of 25% were dispersed in the same MAPOSS acrylate photoresist matrix as in Example 1, but without the addition of any thermally decomposable component (PPC).
[0100] (2) Graphical processing, the same as in Example 1.
[0101] (3) Segmented hard film heat treatment, the same as in Example 1.
[0102] Finally, the temperature was lowered to room temperature at a rate of 2 °C / min to obtain a dense conventional quantum dot photoresist wavelength conversion layer.
[0103] See the schematic SEM cross-sectional image of the conventional quantum dot wavelength conversion layer obtained in this comparative example. Figure 5 and Figure 6 As shown, the structure is dense and without cavities. Testing revealed that, under the same aging conditions, the Micro LED display device based on the conventional quantum dot wavelength conversion layer of Comparative Example 1, after continuous operation at 120 °C for 1000 hours, retained only 61.2% of its quantum dot luminous efficiency (severe thermal quenching), and its brightness decay was significantly higher than that of the sample in Example 1.
[0104] The above are merely preferred embodiments of the present invention and do not limit the scope of protection of the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any changes, modifications, substitutions, integrations, and parameter alterations to these embodiments within the spirit and principles of the present invention, achieved through conventional substitutions or by achieving the same function without departing from the principles and spirit of the present invention, fall within the scope of protection of the present invention.
Claims
1. A photoresist composition, characterized in that, include: Photoresist resin matrix; Wavelength conversion material dispersed in the photoresist resin matrix; Thermally decomposable components dispersed in the photoresist resin matrix; The thermally decomposable component remains stable during the patterning process and decomposes and releases gas during the heat treatment process to form a cavity structure inside the photoresist resin matrix. The cavity structure is filled with the gas generated by pyrolysis, and the refractive index difference Δ between the cavity structure and the photoresist resin matrix is ≥0.
4.
2. The photoresist composition according to claim 1, characterized in that: The decomposition temperature of the thermally decomposable component is higher than the glass transition temperature of the photoresist resin matrix after curing. And / or, the decomposition temperature of the thermally decomposable component is higher than the temperature of the patterning process.
3. The photoresist composition according to claim 1, characterized in that: The thermally decomposable component includes one or a combination of two of thermally decomposable polymers and thermally decomposable small molecules. And / or, the size of the thermally decomposable component is in the nanometer or micrometer range; And / or, the shape of the thermally decomposable component includes spherical, near-spherical, amorphous, or fibrous, with an average particle size of 50~300 nm.
4. The photoresist composition according to claim 3, characterized in that: The thermally decomposable polymers include one or more combinations of polypropylene carbonate, polymethyl methacrylate, polynorbornene polymers, polyterephthalaldehyde, and tert-butyloxycarbonyl modified copolymers. And / or, the pyrolytic small molecule is a small molecule that is incompatible with the photoresist resin matrix at room temperature, and the pyrolytic small molecule includes one or more combinations of azo compounds, carbonate compounds, bicarbonate compounds, tert-butyl ester compounds induced by thermal acid generators, and organic peroxides.
5. The photoresist composition according to claim 1, characterized in that: The wavelength conversion material includes one or more combinations of quantum dots, phosphors, and perovskite nanomaterials; the quantum dots include red quantum dots or green quantum dots. And / or, the photoresist resin matrix is a resin matrix containing a POSS hybrid framework; And / or, the content of wavelength conversion material in the photoresist composition is 10-40 wt%, and the content of thermally decomposable component is 1-15 wt%.
6. A wavelength conversion layer, characterized in that, The wavelength conversion layer has multiple independent cavity structures inside, and the cavity structures are formed by the in-situ decomposition of the thermally decomposable components in the photoresist composition according to any one of claims 1 to 5 through heat treatment.
7. The wavelength conversion layer according to claim 6, characterized in that, include: A photoresist pixel unit formed by curing a resin containing a POSS hybrid framework, the photoresist pixel unit having a nano-confined space formed by the POSS hybrid framework; The in-situ formed closed-cavity structure is uniformly distributed inside the photoresist pixel unit; Wavelength conversion material is continuously distributed in the photoresist pixel unit and distributed around the closed-hole cavity structure; The closed-cell cavity structure is formed by the in-situ pyrolysis of thermally decomposable components within the confined space of the POSS-containing hybrid framework during heat treatment. The POSS-containing hybrid framework restricts the excessive growth and merging of the cavity structure. The closed-cell cavity structure is filled with gas generated by pyrolysis.
8. The wavelength conversion layer according to claim 6, characterized in that, The cavity structure is dispersed within the wavelength conversion layer and does not penetrate the upper and lower surfaces of the wavelength conversion layer; And / or, the size of the cavity structure is in the nanometer or micrometer range; And / or, the cavity structure accounts for 5-25% of the volume of the wavelength conversion layer; And / or, the thickness of the wavelength conversion layer is 1~10 μm.
9. The wavelength conversion layer according to claim 7, characterized in that: The average diameter of the cavity structure is 100~500 nm.
10. A method for fabricating a wavelength conversion layer, characterized in that, include: A wavelength conversion material and a thermally decomposable component are dispersed in a photoresist resin matrix to form a photoresist composition according to any one of claims 1 to 5; The photoresist composition is coated onto a substrate; The photoresist composition is patterned to form a patterned wavelength conversion layer; The patterned wavelength conversion layer is subjected to heat treatment to decompose the thermally decomposable components and form a cavity structure in situ inside the wavelength conversion layer.
11. The preparation method according to claim 10, characterized in that: The cavity structure is formed after the patterning process is completed in the wavelength conversion layer.
12. The preparation method according to claim 10, characterized in that: The heat treatment is a film hardening process, which is a segmented heating heat treatment, including: first heating to 100-140 ℃ at a heating rate of 1-5 ℃ / min and holding for 10-20 min, then heating to 150-230 ℃ at a heating rate of 0.5-3 ℃ / min and holding for 20-40 min; Alternatively, the film-hardening process can be performed by directly heating at a constant temperature of 160~240℃ for 15~60 minutes.
13. A Micro LED display device, characterized in that, include: Light-emitting unit; A wavelength conversion layer disposed on the light-emitting unit; The wavelength conversion layer is the wavelength conversion layer according to any one of claims 6 to 9, or the wavelength conversion layer is prepared on the light-emitting unit by the preparation method according to any one of claims 10 to 12.
